Intramural Ectopic Pregnancy: Clinical Characteristics, Risk Factors for Uterine Rupture and Hysterectomy - Chen, Xiaoran; Gao, Lingyun; Yu, Hongna; Liu, Meijuan; Kong, Shujun; Li, Sijian (Frontiers in Medicine, 2021)
Background: Intramural ectopic pregnancy is defined as the gestational sac (GS) is entirely within the myometrium, separate from the endometrial cavity and fallopian tubes, which is unsustainable and potentially life-threatening. The data investigating the clinical characteristics, management strategy, and fertility outcomes after treatment of intramural ectopic pregnancies are very limited due to its extreme rarity. Methods: To investigate the clinical characteristics, treatment options, and fertility outcomes in patients with intramural ectopic pregnancy, a retrospective study included 56 patients was conducted. We also used logistic regression to identify potential risk factors for uterine rupture and hysterectomy in these patients. Results: The mean age of patients was 31.1 years, with an average gestational age (GA) of 10.0 weeks, and the majority of the patient cohort (83.9%) had uterine or endometrial surgical history. 55.4% of the intramural pregnancy was diagnosed by preoperative imaging examination and 67.7% was detected by ultrasound. There was no dominant predisposed zone of the GS. Common treatment strategies included laparotomy surgery (41.1%) and laparoscopic surgery (35.7%), followed by methotrexate (7.1%) and expectant management (5.4%). Uterine rupture occurred in 9 patients and 8 patients underwent a hysterectomy, but no maternal demise was found. Logistic regression showed that a GA >10 weeks predicted a significantly higher risk of uterine rupture (Odds ratio [OR] 8.000, 95% confidence interval [CI] 1.456 - 43.966, P = 0.017) and hysterectomy (OR 12.333, 95% CI 2.125 - 71.565, P = 0.005), and GS located in the fundus also predicted higher probability of uterine rupture (OR 7.000,95% CI 1.271 – 38.543, P = 0.025). Among the ten patients who had a desire for fertility, 6 of them succeeded and 4 of them successfully delivered with a GA ≥ 34 weeks. Conclusion: GA > 10 weeks was the risk factor for both uterine rupture and hysterectomy, while patients with GS located in the uterine fundus had a significantly higher risk of uterine rupture. The fertility outcomes were moderate after treatment. The management strategies should be individualized according to disease conditions and the desire for fertility, and early diagnosis is essential for optimizing clinical outcomes.